2020
DOI: 10.1017/s1463423620000341
|View full text |Cite
|
Sign up to set email alerts
|

Co-production between long-term care units and voluntary organisations in Norwegian municipalities: a theoretical discussion and empirical analysis

Abstract: Background: In Norway, due to demographic challenges with an ageing population and lower fertility rates, current government policies have encouraged municipalities and volunteers to collaborate. Moreover, present policies recommend an increase in volunteer activities within care services. Co-production is advocated as a functional and innovative method of activating resources when citizens and public employees interact in the care sector. Method: This study has scrutinised ongoing volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The importance of clarifying roles has also been recognized in other studies. 9,11,25 One of the challenges that was initially raised in this action research project was that the nurses, due to capacity issues, could not commit to assist in conducting dog visits. Nevertheless, nurses still had to assist some of the volunteers, leading to frustration because of disruptions in their workplan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of clarifying roles has also been recognized in other studies. 9,11,25 One of the challenges that was initially raised in this action research project was that the nurses, due to capacity issues, could not commit to assist in conducting dog visits. Nevertheless, nurses still had to assist some of the volunteers, leading to frustration because of disruptions in their workplan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted the importance of enthusiasts 34 and having a volunteer coordinator in the care services. 9,11,25 Based on findings from this study, our suggestions for improving dog visit programs to home-dwelling patients would be as follows: 1) do a thorough mapping for appropriate matching of patient preferences and equipages; 2) make a written description of the responsibility and tasks related to the two coordinator roles; 3) have initial and continuous information meetings for the nursing staff and the volunteers; and 4) invite retired nurses to assist visits to the most fragile patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How is the bringing in of volunteers to be organised in a field with professional care workers? Studies so far indicate that voluntary work in LTC is offered and organised differently in municipalities (Rønning, 2011a;Solbjør et al, 2014;Andfossen 2020) or between organisations (Greenfield et al, 2016). For example, a survey of recruitment and follow-up of LTC volunteers in Norway found that less than half of the 429 municipalities had any organised activity in recruiting new volunteers in the care sector (Johansen & Lofthus, 2011).…”
Section: Introductionmentioning
confidence: 99%